Brave - Doyle, Patrick 1953- ([Disney/Pixar], 2012)
Princess Merida, an archer and self-reliant young woman, makes a decision which defies custom and brings chaos to her kingdom. To restore her kingdom, she must rely on her bravery and archery skills
Original: USA 2012
Bonus features: "La luna" theatrical short; "The legend of Mordu" short; Audio commentary
Bildformat 2.39:1 (16:9)
Keywords: Archers / Scotland / Drama; Archers / Scotland / Juvenile drama; Princesses / Drama; Magic / Drama; Magic / Juvenile drama; Animated films; Scotland / Drama; Scotland / Juvenile drama; Archers; Magic; Princesses; Scotland; Computer animation films; Children's films; Drama; Feature films; Fiction films; Juvenile works; Video recordings for people with visual disabilities; Film; DVD-Video